Visualization Studies of the Vortex System Around 3-d Rectangular Buildings - Zucoloto, Stephanie; Queiroz, João; Paula, Reginaldo de; Cezana, Fernanda; Goulart, Elisa; Gomes, Marcos (Ciência e Natura, 2013)
In this work, the vortex system around an isolated prismatic rectangular building was studied using smoke injection technique. This vortex system can be one of the causes of air quality problems, such as dangerous contaminants released in the near wake of the building in chemical-plants. Two models scale building with different aspect ratios were used in an atmospheric boundary wind tunnel. The qualitative analyses of video recorded images of smoke flow and laser light illumination provided a good view of the complex wind flow around an isolated building.